Pengaruh Perspektif Factor Influencing Teaching (FIT) - Choice Theoy terhadap Motivasi Menjadi Guru pada Mahasiswa Keguruan - Chatrisia Ratnasari; Leny Noviani; Sudarno Sudarno (Departement of Mathematics Education, 2024)
The purpose of this research is to investigate: 1) The influence of task perceptions about the teaching profession on the motivation to become a teacher; 2) The influence of confidence in teaching ability on the motivation to become a teacher; 3) The influence of utility value on motivation to become a teacher; 4)The influence of fallback career on motivation to become a teacher; and 5) The combined influence of task perceptions about the teaching profession, confidence in teaching ability, utility value, and fallback career on motivation to become a teacher. Data analysis involves descriptive statistical analysis, multiple linear regression analysis, t-tests, and an F-test. The results of this research indicate that: 1) Task perceptions about teaching professions have a positive and significant effect on the motivation to become a teacher, supported by a t-value of 2.757 > t-table value of 1.97769; 2) Confidence in teaching ability has a positive and significant effect on the motivation to become a teacher, with a t-value of 10.839 > t-table value of 1.97769; 3) Utility value has a positive and significant effect on the motivation to become a teacher, evidenced by a t-value of 13.946 > t-table value of 1.97769; 4) Fallback career has a negative and significant effect on the motivation to become a teacher, indicated by a t-value of -16.871 < t-table value of 1.97769; and 5) FIT Choice Theory have a significant effect on the motivation to become a teacher.